2015
DOI: 10.1007/s00415-015-7870-9
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and meta-analysis of five polymorphisms of the LINGO1 and LINGO2 genes in Parkinson’s disease and multiple system atrophy in a Chinese population

Abstract: Whether polymorphisms rs11856808 and rs9652490 of the Leucine-rich repeat and Ig domain containing, Nogo receptor-interacting protein-1 (LINGO1) gene, as well as rs10968280, rs13362909 and rs7033345 of the LINGO2 gene, increase the risk for Parkinson's disease (PD) is controversial. Considering the overlap of the clinical and pathological characteristics among PD and multiple system atrophy (MSA), we explored the associations between these five polymorphisms and PD and MSA in a Chinese population. A total of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…Ablation of BDNF from the VTA, which projects to NAc, in which neuronal Bdnf gene expression is undetectable 38 , has an antidepressant effect in CSDS 6 similar to AAV-Cre-mediated VGF ablation in NAc shown here. In contrast to targeted AAV-VGF infusion in adult NAc or dHc, more widespread VGF overexpression driven by the CMV-enhancer/chicken beta-actin (CAG) promoter in a single transgenic line resulted in working memory deficits, increased depression-like behavior, reduced striatal volume and brain weight, increased lateral ventricle volume, reduced anxiety, and hyperactivity, although random insertion of this Vgf transgene into Lingo2 , variants of which are associated with Parkinson’s disease 39 41 , resulting in reduced Lingo2 mRNA levels, could also potentially contribute to the phenotype of this line 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Ablation of BDNF from the VTA, which projects to NAc, in which neuronal Bdnf gene expression is undetectable 38 , has an antidepressant effect in CSDS 6 similar to AAV-Cre-mediated VGF ablation in NAc shown here. In contrast to targeted AAV-VGF infusion in adult NAc or dHc, more widespread VGF overexpression driven by the CMV-enhancer/chicken beta-actin (CAG) promoter in a single transgenic line resulted in working memory deficits, increased depression-like behavior, reduced striatal volume and brain weight, increased lateral ventricle volume, reduced anxiety, and hyperactivity, although random insertion of this Vgf transgene into Lingo2 , variants of which are associated with Parkinson’s disease 39 41 , resulting in reduced Lingo2 mRNA levels, could also potentially contribute to the phenotype of this line 42 .…”
Section: Discussionmentioning
confidence: 99%
“…While rs75932628 triggering TREM2 was shown to increase the risk for AD, no association with the risk for MSA was observed [ 117 ]. A meta-analysis suggested that polymorphisms of the LINGO1 and LINGO2 (Nogo receptor-interacting protein-1 and – 2) decrease the risk of PD but not of MSA [ 118 ].…”
Section: Etiology and Geneticsmentioning
confidence: 99%
“…The selectivity of the neurodegeneration in MSA is determined by the concerted interaction of multiple noxious factors, among them ectopic αS accumulation in oligodendrocytes, “prion-like” propagation of misfolded αS, proteasomal and mitochondrial dysfunction [ 8, 124 ], dysregulation of myelin lipids [ 246, 450 ], genetic polymorphism [ 118, 121 ], microglial activation [ 257 ], neuroinflammation [ 261, 451 ], proteolytic disturbance, autophagy [ 191 ]. and other factors contributing to oxidative stress, which is suggested to be a major pathogenic factor in MSA and related diseases [ 452, 453 ].…”
Section: Pathogenesismentioning
confidence: 99%
“…Increased levels of Nogo-A have been reported in schizophrenia (Novak et al, 2002), multiple sclerosis (Satoh et al, 2005), temporal lobe epilepsy (Bandtlow et al, 2004) and Alzheimer’s disease (Gil et al, 2006). An increasing number of mutations and genetic variants in genes depicted in Figure 1 have been found coupled to neuropsychiatric and neurodegenerative disorders, including schizophrenia (NgR1/Nogo-A: Budel et al, 2008; Willi and Schwab, 2013; Andrews and Fernandez-Enright, 2015), (LGI1/NgR1: Thomas et al, 2016), ALS (NgR1: Amy et al, 2015), Pelizaeus-Merzbacher disease (MAG: Lossos et al, 2015), Parkinson’s disease (Lingo-1: Chen et al, 2015), Tourette syndrome/OCD/ADHD (Olfactomedin: Bertelsen et al, 2015) and epilepsy (LgI1: Fukata et al, 2010); (ADAM22: Muona et al, 2016), further emphasizing the importance of normal Nogo-type control of synaptic plasticity. Current knowledge has also led to the initiations of clinical trials in spinal cord injury (NCT00406016), multiple sclerosis (Ineichen et al, 2017), and ALS in which disease a large phase II trial shows no positive effects of Nogo-A antibodies (Meininger et al, 2014).…”
Section: Discussionmentioning
confidence: 99%